PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PENGGUNAAN JASA MELALUI VARIABEL INTERVENING KEPERCAYAAN MEREK ( Studi Kasus Pada JNE Cabang Semarang) - Windy Ramadhani Saputri; Apriatni Endang Prihartini; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2013)
Goals to be achieved in this study was to determine the effect of the decision to use the image of the brand through brand trust services (case study in JNE Branch Semarang). The sample in this research were 100 respondents, respondents are consumers of JNE Branch Semarang. The sampling technique used was purposive sampling. The analysis method used is a simple linear regression and path analysis. Measurement scale using Likert Scale. In the analysis of the data using simple linear regression. From the analysis of the data is known that effect of brand image on the decision to use services is 52,8%, the effect of brand image on brand trust 51,6%, the effect of brand trust on the decision to use services 68,4%, and the effect of brand image to decision to use services through by using brand trust is 1,605. Based on these results JNE Management Branch Semarang should consider consumers' brand trust so that the level of Decision Using JNE. JNE services remains high and Brand Image JNE also remains good.